2016
DOI: 10.17795/compreped-40150
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Tuberculosis among Children and Adolescents at a Referral TB’s Hospital, 2006 - 2011

Abstract: Background: Tuberculosis (TB) is a globally significant cause of morbidity and mortality in children. Few data on tuberculosis in children and adolescents are available in Iran. Objectives: The current study aimed to describe the case characteristics and clinical-epidemiological aspects of children and adolescents with TB. Methods: A retrospective review was undertaken on 203 patients aged less than 19 years admitted to a referral TB hospital from 2006 to 2011. Results: Out of the 203 children and adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
3
2
0
Order By: Relevance
“…In the general population, males are well known to have a higher risk of getting TB than females (Holmes et al, 1998; Borgdorff et al, 2000; Rhines, 2013). The opposite was true in our adolescent population, which was consistent with previous studies (Weber et al, 2000; Bolursaz et al, 2016; Phongsamart et al, 2009). On one hand, this may be explained by difference between lifestyles of the two genders in these two age groups.…”
Section: Discussionsupporting
confidence: 93%
“…In the general population, males are well known to have a higher risk of getting TB than females (Holmes et al, 1998; Borgdorff et al, 2000; Rhines, 2013). The opposite was true in our adolescent population, which was consistent with previous studies (Weber et al, 2000; Bolursaz et al, 2016; Phongsamart et al, 2009). On one hand, this may be explained by difference between lifestyles of the two genders in these two age groups.…”
Section: Discussionsupporting
confidence: 93%
“…74.5% (41/55) of the strains harbored a mutation in codon S531L similar to other studies from Delhi (59–72%) [ 6 , 13 ]. Among 67 INH resistant strains, all except one had a mutation at codon 315 corresponding to high level resistance.…”
Section: Discussionsupporting
confidence: 86%
“…A recent study from Iran has similar findings and showed that prevalence of TB increased by increasing age and the population of female patients also rose [ 12 ]. Similar findings of another study showed that the smear positive pediatric TB was found more often in adolescent girls than boys of the same age [ 13 ].…”
Section: Discussionsupporting
confidence: 84%
“…83% of them had pure pulmonary TB. 17 In the present study, from the total number of pediatric patients, the predominant age group was 13-18 years, with 83 cases (58%). While the number of cases in the age group of less than 7 and 7-12 was 37 and 22 cases, respectively.…”
Section: Resultsmentioning
confidence: 49%